Junior Worldmark encyclopedia of foods and recipes of the world - Hanson, Karen, 1977- (Detroit, MI : U X L, 2002)
Profiles the food, recipes, and culture of sixty countries.
v. 1. Algeria to France -- v. 2. Germany to Japan -- v. 3. Kazakhstan to South Africa -- v. 4. Spain to Zimbabwe, cumulative index.
Includes bibliographical references and index.
Keywords: Food -- Encyclopedias, Juvenile; International cooking -- Encyclopedias, Juvenile; Food -- Encyclopedias; International cooking -- Encyclopedias